Pengaruh Permainan Tradisional Kotak Pos terhadap Perbendaharaan Kata Anak di Taman Kanak-kanak Kartika 1-63 Padang - Shofia, Qatrun Nada; Saridewi, Saridewi (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2019)
Language has an important role in conversational activities that have started early. One aspect of language development that must be developed to support the child's communication process is to increase the child's vocabulary. The purpose of this study is to study traditional post box games on children's vocabulary. This research method uses quantitative methods that are made with quasi-experimental. The population of this research is all children in Kartika Kindergarten 1-63 Padang who received 48 people. The sample used by researchers amounted to 20 children consisting of two classes, each of which consisted of 10 children. The results showed that the children's vocabulary abilities in the experimental group using postal traditional games were on average higher than those in the control group using chain whispers, which were 78.75 experimental classes and 71.87 control classes. That way the traditional postbox game proved to be against the ability of vocabulary in Kartika Kindergarten 1-63 Padang.